Analisis Strengths, Weakness, Opportunity, Threat pada Produk Multiguna di KSPP Syariah Citra Pasundan Utama Bandung - Atje, Reliyani; Rapida, Ida (Jurnal Dimamu, 2024)
Based on the results of observations and interviews, the background of this research is the fluctuating customers that occur in multipurpose products at KSPP Syariah Citra Pasundan Utama Bandung. In connection with this, the author wants to know the position of Multipurpose products by conducting a SWOT analysis. This study aims to determine Strengths, Weakness, Opportunity and threats on multipurpose products at KSPP Syariah Citra Pasundan Utama Bandung so that it can determine the strategy that must be carried out based on the results of EFAS and IFAS analysis.The object of this research aims to find out what are the strengths, weaknesses, opportunities and threats contained in this multipurpose product. The type of research is descriptive qualitative, the type of data is the premier data collection technique in the form of observation, interviews, literature study and documentation study. The results showed that KSPP Syariah Citra Pasundan Utama Bandung's multipurpose products had: 6 items, 6 weaknesses, 6 opportunities, and 6 threats. The analysis results show that the position of multipurpose products is in quadrant I which is aggressive with the Strengths and Opportunity (S-O) pattern and there are 5 strategy points in it.